Predictive factors for postoperative recurrence in early cervical cancer patients: a meta-analysis - Hou, Weili; Ma, Yaru; Sun, Suli; Gao, Yanlei; Ling, Jia; Shi, Rui (Frontiers in Surgery, 2025)
BackgroundEarly-stage cervical cancer generally has a favorable prognosis with treatment, yet recurrence remains a significant risk for a subset of patients. Identifying reliable prognostic factors can help refine risk stratification, optimize follow-up strategies, and guide adjuvant therapy decisions. This meta-analysis evaluates the association between key prognostic factors—tumor diameter, HPV status, depth of invasion, LVSI status, and positive lymph nodes—and recurrence risk in early-stage cervical cancer.Materials and methodsA systematic search of PubMed, Embase, Cochrane Library, and Scopus was conducted to identify studies assessing the relationship between prognostic factors and recurrence in early-stage cervical cancer. Studies meeting predefined inclusion criteria were selected, and data were extracted on patient demographics, tumor characteristics, and recurrence outcomes. The NOS was used to assess study quality. Pooled ORs with 95% CIs were calculated using both fixed-effects and random-effects models, with heterogeneity and publication bias assessed through I² statistics and funnel plot analysis, respectively.ResultsA total of 10 studies were included in the meta-analysis. Tumor diameter >4 cm (OR = 2.49; 95% CI: 1.69–3.69), depth of invasion >1/2 (OR = 2.82; 95% CI: 1.66–4.80), LVSI positivity (OR = 2.54; 95% CI: 1.36–4.73), and positive lymph nodes (OR = 2.86; 95% CI: 1.99–4.11) were all significantly associated with an increased risk of recurrence. However, HPV-positive status showed no consistent association with recurrence risk (OR = 2.12; 95% CI: 0.31–14.52), likely due to high heterogeneity among the studies (I² = 86%). Sensitivity analyses confirmed the robustness of the results, and publication bias was minimal.ConclusionThis meta-analysis identified tumor diameter >4 cm, depth of invasion >1/2, LVSI positivity, and positive lymph nodes as significant prognostic factors for recurrence in early-stage cervical cancer. These findings underscore the importance of comprehensive assessment in clinical practice to better identify high-risk patients who may benefit from intensified monitoring or adjuvant therapies. Further research, particularly on the role of HPV status, is needed to enhance the predictive accuracy of recurrence risk models.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024599867, PROSPERO CRD42024599867.